Molecular mechanisms and genetic factors contributing to the developmental dysplasia of the hip - Zhao, Xiaoming; Liu, Shuai; Yang, Zhonghua; Li, Yong (Frontiers in Genetics, 2024)
The most prevalent hip disease in neonates is developmental dysplasia of the hip (DDH). A timely and accurate diagnosis is required to provide the most effective treatment for pediatric patients with DDH. Heredity and gene variation have been the subject of increased attention and research worldwide as one of the factors contributing to the pathogenesis of DDH. Genome-wide association studies (GWAS), genome-wide linkage analyses (GWLA), and exome sequencing (ES) have identified variants in numerous genes and single-nucleotide polymorphisms (SNPs) as being associated with susceptibility to DDH in sporadic and DDH family patients.Furthermore, the DDH phenotype can be observed in animal models that exhibit susceptibility genes or loci, including variants in CX3CR1, KANSL1, and GDF5. The dentification of noncoding RNAs and de novo gene variants in patients with DDH-related syndrome has enhanced our understanding of the genes implicated in DDH. This article reviews the most recent molecular mechanisms and genetic factors that contribute to DDH.